Effective AAV-mediated gene replacement therapy in retinal organoids modeling AIPL1-associated LCA4 - Hali Sai; Bethany Ollington; Farah O. Rezek; Niuzheng Chai; Amelia Lane; Anastasios Georgiadis; James Bainbridge; Michel Michaelides; Almudena Sacristan-Reviriego; Pedro R.L. Perdigão; Amy Leung; Jacqueline van der Spuy (Elsevier, 2024)
Biallelic variations in the aryl hydrocarbon receptor interacting protein-like 1 (AIPL1) gene cause Leber congenital amaurosis subtype 4 (LCA4), an autosomal recessive early-onset severe retinal dystrophy that leads to the rapid degeneration of retinal photoreceptors and the severe impairment of sight within the first few years of life. Currently, there is no treatment or cure for AIPL1-associated LCA4. In this study, we investigated the potential of adeno-associated virus-mediated AIPL1 gene replacement therapy in two previously validated human retinal organoid (RO) models of LCA4. We report here that photoreceptor-specific AIPL1 gene replacement therapy, currently being tested in a first-in-human application, effectively rescued molecular features of AIPL1-associated LCA4 in these models. Notably, the loss of retinal phosphodiesterase 6 was rescued and elevated cyclic guanosine monophosphate (cGMP) levels were reduced following treatment. Transcriptomic analysis of untreated and AAV-transduced ROs revealed transcriptomic changes in response to elevated cGMP levels and viral infection, respectively. Overall, this study supports AIPL1 gene therapy as a promising therapeutic intervention for LCA4.